The wage-price-productivity nexus - Bodkin, Ronald G. (Philadelphia : University of Pennsylvania Press, 1966)
The author attempts to analyze the wage and price structure of an important segment of American economy. A strong motivating force has been a concern with basic economic goals; the compatibility or incompatibility of the goals of full employment and price level stability was, in the author's view, a fundamental issue.
A revision of the author's thesis, University of Pennsylvania.
Includes bibliographical references: p. 285-296.
rpm 22/02/2018
Loans
Keywords: Wages and labor productivity; Prices